1970
DOI: 10.1126/science.167.3919.882
|View full text |Cite
|
Sign up to set email alerts
|

Striated Muscle Fibers: Inactivation of Contraction Induced by Shortening

Abstract: The myofibrils in an isolated muscle fiber remain straight during the early part of a lightly loaded contraction initiated by membrane depolarization, but, as shortening continues, myofibrils in the core of the fiber become wavy, which suggests that their activation has been interrupted by shortening of the fiber. This may be a factor determining the length-tension relation at short muscle lengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

1972
1972
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(52 citation statements)
references
References 16 publications
2
49
1
Order By: Relevance
“…Finally, analyses of the ATP hydrolysis of foreshortened muscles are not measurements of the activation metabolism per se as such measurements must include an energy consumption due to residual actomyosin interaction. Further, Taylor & Rudel (1970) have suggested that at sarcomere lengths less than 1-6 ,u the activation mechanism is inhibited. Tension-related heat.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, analyses of the ATP hydrolysis of foreshortened muscles are not measurements of the activation metabolism per se as such measurements must include an energy consumption due to residual actomyosin interaction. Further, Taylor & Rudel (1970) have suggested that at sarcomere lengths less than 1-6 ,u the activation mechanism is inhibited. Tension-related heat.…”
Section: Discussionmentioning
confidence: 99%
“…A possibility worth considering would be that the relatively wide frog muscle fibers become incompletely activated during tetanic stimulation at short lengths because of decremental inward spread of activation as the fiber diameter expands with shortening (Taylor and Rüdel, 1970; however, see GonzalezSerratos, 1975). This would reduce the force output below the expected values along the ascending limb in the frog fibers.…”
Section: The Length-tension Relationshipmentioning
confidence: 99%
“…Below the slack length, both isometric tension and speed of unloaded shortening fall off steeply, and although some of the features of this 18 A. F. HUXLEY MUSCULAR CONTRACTION decline seemed to be related to the length of the filaments (Gordon et al 1966b), it is now clear that a failure of inward spread of activation is at least part of the explanation (S. R. Taylor & RUdel, 1970; RUdel & S. R. ).…”
Section: Sliding Filamentsmentioning
confidence: 99%